IMPACTS OF MATHEMATICAL SKILLS ON NATIONAL SECURITY - Charles-Ogan Gladys (European Scientific Journal, ESJ, 2014)
The utilization of mathematical skills in the nation’s security systems is highlighted. The various forms of security and the role that mathematics plays in each of them are examined. Thus it is being recommended that there should be effective and functional mathematics education at all levels so as to transform skills realized for mathematics to solve the nation’s security challenges.